2018
DOI: 10.3390/cryst8110429
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electronic, Magnetic, Mechanic and Thermodynamic Properties of the Inverse Heusler Alloy Ti2NiIn Under Pressure

Abstract: Structural, electronic, magnetic and mechanic properties of the inverse Heusler alloy Ti2NiIn under different pressure are systematically studied with density functional theory (DFT). The equilibrium lattice constant and electronic band structure at null pressure are obtained to be consistent with previous work. Under currently applied static pressure from 0 GPa to 50 GPa, it is found that the half-metallicity of the material is maintained and the total magnetic moment (Mt) is kept at 3 µB, which obeys the Sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The HAs are remarkable due to their active role in the spin‐injection devices, 13‐17 spintronic devices and high thermoelectric performance, 18‐20 tunnelling magneto‐resistance, 21‐24 spin filters, 16 giant magneto resistance, 25,26 magnetic sensors, 27 non‐volatile magnetic random access memories, 28,29 electro‐mechanical applications 30 . The extensive theoretical 31‐35 and experimental 36‐40 studies of the HAs have been reported in the literature in context to the thermoelectric applications due to their high power factor and low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…The HAs are remarkable due to their active role in the spin‐injection devices, 13‐17 spintronic devices and high thermoelectric performance, 18‐20 tunnelling magneto‐resistance, 21‐24 spin filters, 16 giant magneto resistance, 25,26 magnetic sensors, 27 non‐volatile magnetic random access memories, 28,29 electro‐mechanical applications 30 . The extensive theoretical 31‐35 and experimental 36‐40 studies of the HAs have been reported in the literature in context to the thermoelectric applications due to their high power factor and low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%
“…During material preparation, the distortion of the crystal structure often happens, and this situation is especially prevalent in thin-film growth. The electronic and magnetic properties are strongly related with the structures of materials and they could experience large changes under structural distortions [12,25]. Herein, we further evaluate the effects of uniform and tetragonal strains for CoFeMnSi.…”
Section: Strain Effectsmentioning
confidence: 99%
“…Consequently, various Heusler compounds can be simply designed by substituting with an element from the same group in the periodic table. For a full-Heusler alloy, when the highly ordered cubic structure is considered under normal conditions, there are two typical structural configurations [12,25]: the first one is the Cu 2 MnAl-type, also known as the L2 1 structure; the second one is the Hg 2 CuTi-type, also known as the XA structure.…”
Section: Introductionmentioning
confidence: 99%
“…The family of Heusler alloys has attracted much scientific attention and research interest during recent years, and their various and special functionalities have been extensively studied and explored in many different areas. The ferromagnetism was firstly observed in Heusler compounds with no ferromagnetic elements and, afterwards, many more new properties have been found, such as half metallicity [1][2][3][4][5][6][7][8][9][10], spin gapless semiconductivity [11][12][13][14][15][16][17], thermoelectricity [18][19][20][21][22][23], superconductivity [24][25][26], and topological insulativity [27,28]. Also, these properties can be easily tuned by simple element substitution within the periodic table.…”
Section: Introductionmentioning
confidence: 99%